Quantitative Phylogenetic Analysis in the 21st Century - Jaret Bilewitch (Universidad Nacional Autónoma de México, 2007)

(untitled) (Revista Mexicana de Biodiversidad)
We review Hennigian phylogenetics and compare it with Maximum parsimony, Maximum likelihood, andBayesian likelihood approaches. All methods use the principle of parsimony in some form. Hennigian-based approachesare justified ontologically by the Darwinian concepts of phylogenetic conservatism and cohesion of homologies, embodiedin Hennig is Auxiliary Principle, and applied by outgroup comparisons. Parsimony is used as an epistemological tool,applied a posteriori to choose the most robust hypothesis when there are confl icting data. Quantitative methods useparsimony as an ontological criterion: Maximum parsimony analysis uses unweighted parsimony, Maximum likelihoodweight all characters equally that explain the data, and Bayesian likelihood relying on weighting each character partitionthat explains the data. Different results most often stem from insufficient data, in which case each quantitative methodtreats ambiguities differently. All quantitative methods produce networks. The networks can be converted into trees byrooting them. If the rooting is done in accordance with Hennig is Auxiliary Principle, using outgroup comparisons, theresulting tree can then be interpreted as a phylogenetic hypothesis. As the size of the data set increases, likelihood methodsselect models that allow an increasingly greater number of a priori possibilities, converging on the Hennigian perspectivethat nothing is prohibited a priori. Thus, all methods produce similar results, regardless of data type, especially when theirnetworks are rooted using outgroups. Appeals to Popperian philosophy cannot justify any kind of phylogenetic analysis,because they argue from effect to cause rather than from cause to effect. Nor can particular methods be justifi ed on thebasis of statistical consistency, because all may be consistent or inconsistent depending on the data. If analyses usingdifferent types of data and/or different methods of phylogeny reconstruction do not produce the same results, more dataare needed.